(untitled) (Journal of Science Foundation, 2013)
Investigation of the static lateral load resistance of pile on layered sandy soil was made by laboratory model test on single pile. The experiment was carried out with variable diameter and variable embedded length of pile on sandy soil. In this study, model pile was single pile which satisfies the Meyerhofs Relative Stiffness limit of pile for flexible pile. Single pile embedded length, L=0.46m, 0.609m, 0.762m for pile diameter, d=0.013m, 0.019m, 0.026m, respectively. And for surcharge condition embedded length of single pile, L=0.609m and surcharge of pressure, P=3369.55Kg/m3, P=6739.1 Kg/m3 and P=13478.20Kg/m3 for each diameter and for saturated condition of pile diameter, d=0.013m. These experiments were conducted with local sand of Rajshahi region and domar sand; available in Bangladesh. Lateral static loads were applied in the single by a static lateral load set up arrangement. Due to the static lateral load the pile was deflected. The load-displacement response, ultimate resistance of pile has been qualitatively and quantitatively investigated in the experiment. The lateral resistance of pile obtains by experiment and the ultimate lateral load resistances obtained by analytical methods were compared. The load displacement curves are similar and non-linear. Lateral failure at a pile head displacement from 8 to 10, 7 to 9 and 6 to 8mm for single pile of d= 0.013m, 0.019m and 0.026m, respectively. In the case of saturated condition of sand a pile head displacement 15mm for single of d=0.013m. It observed that the failure load was the point at which the curve exhibits a pick or maintains continuous displacement increase with no further increase in lateral resistance. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14630 J. Sci. Foundation, 8(1&2): 83-88, June-December 2010